Application of the Simple Multi Attribute Rating Technique (SMART) Method on the Selection of Anti Mosquito Lotion based on the Consumer - Indra Riyana Rahadjeng (IJISTECH (International Journal of Information System and Technology), 2020)
The purpose of this study is to select the best anti-mosquito lotion based on consumers by utilizing decision support system techniques. The method used is the Simple Multi Attribute Rating Technique (SMART). The research data were obtained by observing, interviewing and administering random questionnaires to 150 respondents. The location of the study was conducted in Pondok Cina, Beji District, Depok City, West Java. The results of the questionnaire will be processed first by using Microsoft Excel before using the SMART method in completion. From the questionnaire distribution, several assessment criteria were obtained in the selection of anti-mosquito lotions, namely: Product Safety (C1), Price (C2), Product Quality (C3), Halal Label (C4), Product Health. While the alternatives used in the selection of anti-mosquito lotions based on observations, interviews and questionnaires are: Soffel (A1), Lavenda (A2), Caladine (A3), Autan (A4) and Neem Lotion (A5). the results of the calculation of the SMART method obtained alternative Autan (A4) as the best alternative for anti-mosquito lotion with a value (48.31). The results of the election can be used as information for users of anti-mosquito lotions.